2013
DOI: 10.1111/ele.12144
|View full text |Cite|
|
Sign up to set email alerts
|

Rates of projected climate change dramatically exceed past rates of climatic niche evolution among vertebrate species

Abstract: A key question in predicting responses to anthropogenic climate change is: how quickly can species adapt to different climatic conditions? Here, we take a phylogenetic approach to this question. We use 17 time-calibrated phylogenies representing the major tetrapod clades (amphibians, birds, crocodilians, mammals, squamates, turtles) and climatic data from distributions of > 500 extant species. We estimate rates of change based on differences in climatic variables between sister species and estimated times of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
300
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(326 citation statements)
references
References 47 publications
11
300
1
1
Order By: Relevance
“…For instance, Deutsch et al [3] showed that terrestrial ectotherms, which have distributions determined by a narrow thermal variation tolerance, would be highly sensitive to temperature changes. Similarly, Quintero & Wiens [2] found that most locally adapted vertebrate species probably evolve too slowly to overcome the global warming expected in the next century. Finally, many thermal-dependent fitness components varying among populations are correlated with local climatic conditions in diverse species (e.g.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, Deutsch et al [3] showed that terrestrial ectotherms, which have distributions determined by a narrow thermal variation tolerance, would be highly sensitive to temperature changes. Similarly, Quintero & Wiens [2] found that most locally adapted vertebrate species probably evolve too slowly to overcome the global warming expected in the next century. Finally, many thermal-dependent fitness components varying among populations are correlated with local climatic conditions in diverse species (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Among these changes, global warming is expected to be a major source of biome perturbation in the next 100 years. During this period, warming could exceed the range of temperatures that many living organisms can tolerate [1,2], especially in taxa that exhibit low adaptability to temperature change. For instance, Deutsch et al [3] showed that terrestrial ectotherms, which have distributions determined by a narrow thermal variation tolerance, would be highly sensitive to temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…126 and 128). If restricted to in situ evolution, many tetrapods will not survive projected warming unless rates of adaptation accelerate more than a thousandfold above those observed paleontologically (133).…”
Section: Proxy Evidence Of (Paleo)environmentalmentioning
confidence: 99%
“…Divergence-time estimation has become a fundamental aspect of phylogenetic analysis, especially since many analyses of character evolution, diversification, and biogeography now utilize (or require) time-calibrated trees (e.g. Ricklefs, 2007;Ree and Smith, 2008;FitzJohn, 2010;Quintero and Wiens, 2013). Therefore, understanding how missing data impact divergencetime estimation is increasingly important and urgent.…”
Section: Introductionmentioning
confidence: 99%